GDP-Mannose 3,5-Epimerase: A View on Structure, Mechanism, and Industrial Potential - Beerens, Koen; Gevaert, Ophelia; Desmet, Tom (Frontiers in Molecular Biosciences, 2022)
GDP-mannose 3,5-epimerase (GM35E, GME) belongs to the short-chain dehydrogenase/reductase (SDR) protein superfamily and catalyses the conversion of GDP-d-mannose towards GDP-l-galactose. Although the overall reaction seems relatively simple (a double epimerization), the enzyme needs to orchestrate a complex set of chemical reactions, with no less than 6 catalysis steps (oxidation, 2x deprotonation, 2x protonation and reduction), to perform the double epimerization of GDP-mannose to GDP-l-galactose. The enzyme is involved in the biosynthesis of vitamin C in plants and lipopolysaccharide synthesis in bacteria. In this review, we provide a clear overview of these interesting epimerases, including the latest findings such as the recently characterized bacterial and thermostable GM35E representative and its mechanism revision but also focus on their industrial potential in rare sugar synthesis and glycorandomization.